Development Of A 2d Educational Animal Card Game Using Unity: Pengembangan Game Kartu Hewan Edukatif 2D Menggunakan Unity - Alma Sulaiman; Mamay Syani (NUANSA INFORMATIKA, 2025)
This research focuses on the development of Game Kartu Hewan, a 2D educational game for kindergarten children at TK Assalam Parongpong, using Unity and the Multimedia Development Life Cycle (MDLC). The study aimed to create an engaging learning tool for animal recognition (names and sounds). The MDLC method guided the game's creation through concept, design, material collection, assembly, and testing phases. Testing involved 90 kindergarten children (aged 3–6 years) and 10 teachers through game interaction, observation, interviews, and pre-test/post-test analysis. Results showed a significant improvement in animal recognition ability, with the average score increasing from 58.4 (pre-test) to 84.7 (post-test). A total of 85% of students completed all levels of the game, and 91% successfully identified animal names and sounds. The majority of children reported enjoying the game and found it easy to play. Teachers' feedback also emphasized the game's effectiveness as an educational tool. This study underscores the efficacy of Unity-based 2D games developed via MDLC in fostering engaging and effective learning experiences for young children.